Early focality and spread of cortical dysfunction in amyotrophic lateral sclerosis: A regional study across the motor cortices. Issue 4 (April 2020) - Dharmadasa, Thanuja; Matamala, José M.; Howells, James; Vucic, Steve; Kiernan, Matthew C.
Highlights: Cortical dysfunction was explored from multiple motor regions across hemispheres in ALS patients. Early cortical dysfunction was focal and asymmetric, mirroring asymmetrical clinical onset. Global dysfunction was apparent in later disease, with regional differences linked to clinical heterogeneity. Abstract: Objective: To characterise the regional cortical patterns underlying clinical symptomatology in amyotrophic lateral sclerosis (ALS). Methods: 138 patients prospectively underwent transcranial magnetic stimulation studies from hand and leg cortical regions of each hemisphere, obtaining motor evoked potentials from all four limbs. Patients were categorised by clinical phenotype and underwent clinical and peripheral evaluation of disease. Results: Cortical dysfunction was evident across the motor cortices, with reduction in short-interval intracortical inhibition (SICI) suggesting the presence of widespread cortical hyperexcitability, most prominently from clinically affected regions (hand p  < 0.0001; leg p  < 0.01). In early disease, cortical abnormalities were asymmetric between hemispheres, focally corresponding to clinical site-of-onset ( p  < 0.05). Degrees of cortical dysfunction varied between phenotypes, with the bulbar-onset cohort demonstrating greatest reduction in SICI ( p  = 0.03). Conclusions: The pattern of cortical dysfunction appears linked to clinical evolution in ALS, with early focal asymmetry preceding widespread changes in later disease. Cortical differences across phenotypes may influence clinical variability. Significance: This is the first study to extensively map cortical abnormalities from multiple motor regions across hemispheres. The early cortical signature mirrors symptom laterality, supporting a discrete region of disease onset. Phenotypes appear to exist within a pathophysiological continuum, but cortical heterogeneity may mediate observed differences in clinical outcome.